Urbanization brings earlier onset of summertime compound heatwaves - Peng Ji; Xinyi Zhang; Xing Yuan; Qibo Xu (Communications Earth & Environment)
Abstract Urbanization is revealed to cause more frequent and hotter day-night compound heatwaves, yet its impact on their onset remains unclear. This study compares summertime compound heatwaves in 722 urban-rural station pairs globally on an event-by-event basis during 1971-2017 and attributes their difference to numerous urbanization and climatological factors using interpretable machine learning methods. Here we find a discernible earlier onset (0.23 ± 0.04 days) of compound heatwaves in cities compared to rural areas. The magnitude of this influence is primarily determined by urban building volume and height rather than the artificial impervious surface fraction, and is exacerbated by climates characterized by warm night and ample daytime solar radiation. Taller buildings significantly advance onset in cloudy, warm, and humid climates, while larger building volumes lead to earlier onset of compound heatwaves across nearly all climates. Our findings suggest that cities, particularly those with large building volumes, should issue heatwave warnings earlier.